Phenotypic Ultra-Rapid Antimicrobial Susceptibility Testing for Ceftazidime–Avibactam: In Support of Antimicrobial Stewardship - Inês Martins-Oliveira; Blanca Pérez-Viso; Rosário Gomes; David Abreu; Ana Silva-Dias; Rafael Cantón; Cidália Pina-Vaz (Microorganisms)
Ceftazidime–avibactam (CZA) is a potent broad-spectrum drug combination covering extended-spectrum β-lactamases, AmpC, and carbapenemases of class A and D, OXA-48-type producers. Rapid antimicrobial susceptibility testing is crucial for the timely de-escalation/escalation of therapy. We evaluate CZA susceptibility using the CE-IVD FASTgramneg kit (FASTinov®), a ground-breaking 2 h assay, based on flow cytometry technology for antimicrobial susceptibility testing. The assay involved rapid bacterial extraction and purification from positive blood cultures (PBCs), followed by a 1 h 37 °C incubation and flow cytometry analysis (Cytoflex, Beckman-Coulter). The susceptibility report was generated using a proprietary software and interpreted using EUCAST and CLSI 2024 criteria. Sensitivity and specificity were calculated against a reference standardized method (disk diffusion) according to ISO20776-2:2021. Overall, 135 Enterobacterales and 73 Pseudomonas aeruginosa isolates were studied. Thirty-four isolates were resistant to CZA, including six P. aeruginosa and 28 Enterobacterales (24 metallo-beta-lactamase producers, three KPC variants, and one co-producing KPC+NDM). Sensitivity and specificity reached 100% when using EUCAST and CLSI criteria compared with the reference method. The FASTinov ultra-rapid susceptibility assay for CZA demonstrated excellent results, potentially enabling de-escalation/escalation even before the second dose. Combining the speed of a molecular assay with the comprehensive information of a phenotypic test offers valuable insights for treatment decisions.